Profil Dan Analisis Usaha Penggilingan Padi Heler Dapan Di Desa Balingka, Kecamatan IV Koto, Kabupaten Agam, Sumatera Barat - Iqbal kurniawan; Harun Arrahman; Nabila Anisafira; Zulfitri Yani; Sularno Sularno (CV. ITTC INDONESIA, 2026)
Rice milling (heler) is an essential component of the rural food supply chain in Indonesia. This descriptive study presents the profile, operations, and development potential of Heler Dapan, a micro-scale rice milling enterprise independently managed by Hadi Rahmanda in Balingka Village, IV Koto District, Agam Regency, West Sumatra. Data were collected through direct observation, business website documentation, and informal interviews with the owner. The findings indicate that Heler Dapan provides rice milling services, grain cleaning and sorting, as well as weighing and loading services, with main products including Kuriak Kusuik Rice (IDR 180,000/unit), Lawang Rice (IDR 170,000/unit), and livestock bran (IDR 2,000/kg). The business operates without permanent employees, running daily from 08:00 to 17:00 local time, serving farmers and collectors in Balingka Village and surrounding areas. Although classified as a micro-enterprise, Heler Dapan holds strategic value in ensuring the availability of quality local rice and the utilization of agro-industrial by-products. Capacity development through marketing digitalization, financial recordkeeping, and product diversification has significant potential to improve the business's competitiveness.